Origin of work function modification by ionic and amine-based interface layers - Reenen, Stephan van; Kouijzer, Sandra; Janssen, René A. J.; Wienk, Martinus Maria; Kemerink, Martijn (Advanced materials interfaces, 2014)
Work function modification by polyelectrolytes and tertiary aliphatic amines is found to be due to the formation of a net dipole at the electrode interface, induced by interaction with its own image dipole in the electrode. In polyelectrolytes differences in size and side groups between the moving ions lead to differences in approach distance towards the surface. These differences determine magnitude and direction of the resulting dipole. In tertiary aliphatic amines the lone pairs of electrons are anticipated to shift towards their image when close to the interface rather than the nitrogen nuclei, which are sterically hindered by the alkyl side chains. Data supporting this model is from scanning Kelvin probe microscopy, used to determine the work function modification by thin layers of such materials on different substrates. Both reductions and increases in work function by different materials are found to follow a general mechanism. Work function modification is found to only take place when the work function modification layer (WML) is deposited on conductors or semiconductors. On insulators no effect is observed. Additionally, the work function modification is independent of the WML thickness or the substrate work function in the range of 3 to 5 eV. Based on these results charge transfer, doping, and spontaneous dipole orientation are excluded as possible mechanisms. This understanding of the work function modification by polyelectrolytes and amines facilitates design of new air-stable and solution-processable WMLs for organic electronics.
Gesehen am 09.12.2019